Efektivitas Metode Pembelajaran Mnemonik Terhadap Kemampuan Mengahafal Rumus-Rumus Fisika - Jusriana, Andi; Anggereni, Santih; Jurdah Budiman, Arham (Al-Khazini, 2022)
The ability to memorize has an important role in the educational process, because the ability to memorize formulas students can remember what has been learned in physics lessons which many formulas in memorizing memory are needed, low memory interferes with students in learning, especially in physics subjects that require students to master the formulas of physics subjects that have many formulas. This research model is an experiment using one class with two trials, the first meeting using the lecture method and then being tested, then using the mnemonic method and then being tested, the number of samples is 27 students. variable x in this study is the mnemonic method and variable y is the ability to memorize physics formulas. This research design uses the Equivalent Time – Samples Design where the ability to memorize physics formulas is seen from the initial test and the second test using different methods, namely the lecture method and Mnemonic. There are 10 number of questions that are used as initial test questions in the lecture method and 10 questions on the Mnemonic method and all questions are valid. The reliability value obtained is 0.95, it shows a high reliability value. The average value using the lecture method is 46.67 with a standard deviation of 16, 17 and the Mnemonic method 90.74 with a standard deviation of 8.28. Based on non-parametric statistical hypothesis testing, obtained by the lecture method and the Mnemonic method, namely 6.2. These results show that students' ability to memorize physics formulas after being taught by the Mnemonic method is better than the lecture method.